ROLES OF THE DIASPORA CHRISTIANS IN MISSION AND EVANGELISM FROM AN AFRICAN ORTHODOX PERSPECTIVE - NJOROGE, John N. (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2021)
This paper will focus on the specific roles that the diaspora orthodox Christian can play in mission and evangelism today. The main objective is to bring into the attention, and especially from a missiological point of view, the fact that the diaspora Christians can have an active role to play in the mission of the church. The active Orthodox Church missions has been understand to mean overseas mission and especially in Africa, Asia and in the Albania. However, in the course of the orthodox Christian migration history, there has been missiological connection between the diaspora Christians in the hosting countries and their respective home countries. The focus of this paper is on this missiological connection and how it can translate to an active role of the involved Christians to the mission of the church in Africa. The paper tracks the mission praxis of the diaspora Christians in Africa and beyond.